Experimental Study of the Thermal Performance of Flat Plate Solar Collectors Array by Different Connection Configurations - Jafar Mehdi Hassan, Prof. Dr.; Qussai Jihad Abdul-Ghafour, Ass. Prof. Dr.; Mohammed Fowzi Mohammed, Instructor (Journal of Engineering, 2015)
The current research illustrates experimentally the effect of series and parallel connection (Z-I Configurations) of flat plate water solar collectors array on the thermal performance of closed loop solar heating system. The study includes the effect of changing the water flow rate on the thermal efficiency. The results show that, the collector's efficiency in series connection is higher than the parallel connection within flow rate level less than (100) ℓ/hr. Moreover, the collector efficiency in parallel connection of (I-Configurations) is more than the (Z- Configurations) with increasing the water flow rate .The maximum daily efficiency for parallel (I-Configurations) and (Z- Configurations) are (55%) and (51%) at water flow rate (150) ℓ/ hr. It was also noted that the thermal stratification of storage tank in case of series connection is higher than that of parallel connection. Also, when the flow rate increases, the thermal stratification of storage tank reduces.